In the nature of landscape : cultural geography on the Norfolk Broads - Matless, David (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2014)
"Covers a great diversity of topics, from popular culture to scientific research, folk song to holiday diaries, planning survey to pioneering photography, and ornithology to children's literature"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Human geography -- England -- Broads, The; Landscapes -- England -- Broads, The; SCIENCE -- Earth Sciences -- Geography; Ecology; Historical geography; Human geography; Landscapes; Manners and customs; Broads, The (England) -- Social life and customs; Broads, The (England) -- Historical geography; Broads, The (England) -- Environmental conditions; England -- Broads, The; Electronic books